A rhetorical cristism of speeches delivered by Dr Zeti Akhtar Aziz on the issues of Islamic banking and finance locally - Khor, Mi Nee; Ahmad, Abdul Mua'ti @ Zamri; Mahamed, Mastura (IKRAM Education, 2013)
Malaysian International Islamic Financial Centre was set up by Malaysian government to transform Malaysia into a vibrant International Islamic Financial hub. Malaysian Central Bank plays an important role in this transformation. One of the efforts is through the formal speeches delivered by the Central Governor, where it could be used to create and direct the necessary actions. Their speeches within and outside the company are important in motivating others and gaining support for their plan (Hartog, 1997). This study was designed to discover the application of the canon of logos by Malaysian Central Bank Governor, Dr. Zeti Akhtar Aziz. A modified version of neo Aristotelian criticism was used to analyse three formal speeches delivered locally with the focus of Islamic Finance products and services, from 2002 to 2006. This analysis indicated that Dr. Zeti only applied four types of proofs in her speeches; example of quantification, explanations, fact and serial examples. It could be due to the audiences, who were mostly local where they were exposed to the extensive exposure and education program on the Islamic banking done by local commercial banks. Practically, this study could assist and guide corporate leaders, especially those from banking industry to advance their business rhetorical skills in a more practical way.